СОЦИОКУЛЬТУРНЫЕ АСПЕКТЫ НЕКОТОРЫХ ПОНЯТИЙ В АНГЛИЙСКОМ ЯЗЫКЕ - Рзаева, Р.К.; Ешимбетова, Н.М. (SCIENCE and SOCIETY, 2016)
The article deals with the issues of linguoculturology, one of the actual branches formed on the basis of interaction of language and culture. There have been analysed the sociocultural aspects and lexical detalization of some English concepts on the material of the literary works. The results of the investigation show, that such concepts as «tasty», «untasty», «clean», «dirty» are expressed in various ways, they are sociolinguistically-conditioned and express customs, traditions, etiquette and other norms of the society.
Keywords: linguoculturology; sociolinguistics; language and culture; sociocultural aspects; sociocultural competence; traditions and customs; socio-linguistically-conditioned; concept; overstatement